1984
DOI: 10.1073/pnas.81.23.7599
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of hepatic low density lipoprotein receptors by radionuclide scintiscanning in vivo.

Abstract: The low density lipoprotein (LDL) receptor mediates the cellular uptake of plasma lipoproteins that are derived from very low density lipoproteins (VLDL). Most of the functional LDL receptors in the body are located in the liver. Here, we describe a radionuclide scintiscanning technique that permits the measurement of LDL receptors in the livers of intact rabbits. '231-labeled VLDL were administered intravenously, and scintigraphic images of the liver and heart were obtained at intervals thereafter. In seven n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Hybridization analysis showed that LR11 expression in liver from WHHL rabbits did not differ from that in normal rabbits (Fig. 6B), despite a 6 -10-fold difference in serum cholesterol levels (Huettinger et al, 1984), clearly indicating that LR11 expression is not affected by cholesterol levels in vivo.…”
Section: Tissue-specific Expression and Regulatory Features Of Lr11-mentioning
confidence: 89%
“…Hybridization analysis showed that LR11 expression in liver from WHHL rabbits did not differ from that in normal rabbits (Fig. 6B), despite a 6 -10-fold difference in serum cholesterol levels (Huettinger et al, 1984), clearly indicating that LR11 expression is not affected by cholesterol levels in vivo.…”
Section: Tissue-specific Expression and Regulatory Features Of Lr11-mentioning
confidence: 89%
“…Plasma fatty acids can enter liver when unesterified by passive diffusion or facilitated transport (49,50) or via hepatocyte lipoprotein receptors when esterified within lipoproteins (51)(52)(53)(54)(55)(56). The dilution coefficient l a-LNA-CoA (equation 4) equals the steady-state rate of entry of unesterified plasma a-LNA into the liver a-LNA-CoA pool, divided by the sum of this rate and rates of entry via plasma lipoproteins and from deacylation of stable lipids (because a-LNA cannot be synthesized de novo, its synthesis makes no contribution to a-LNA-CoA) (11,12,28).…”
Section: Discussionmentioning
confidence: 99%
“…The liver biopsy preparation (at day 119 after HcTx) and onedimensional electrophoresis in 5-10% SDS-polyacrylamide gradient slot gels (protein w20 mg/slot) in the absence of reducing agents was carried out as previously described [21][22][23]. Proteins from SDS slab gels were transferred by electroblotting to a nitrocellulose membrane.…”
Section: Immunoblot Detection Of Ldl Receptor Proteinsmentioning
confidence: 99%